Transparency in sustainability reporting: a case study of Natura Cosméticos S.A. on the practice of voluntary disclosure - Kanda , Jorge Yoshio; Bandeira, Miriã Michaela de Souza (Sustainability in Debate, 2025)
Sustainability reports stand out as key communication tools for environmental, social, and economic issues with stakeholders, meeting the demands of a market to integrate environmental considerations into organisational practices. The objective of this research is to analyse the level of transparency in sustainability reports and the reliability of information in Natura Cosméticos S.A.'s annual disclosures. This research is classified as exploratory qualitative and incorporates an analysis of documents by examining Natura Cosméticos S.A.'s sustainability reports from 2020 to 2023. The results reveal a selectivity of information, prioritising optimistic disclosures to favour the company's self-image and the maintenance of its social contract. This research contributes to scientific advancement in the field of environmental management and encourages interdisciplinary studies focused on legitimate transparency.